2014
DOI: 10.1021/ac503290j
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Profiling of Tracer-Derived Metabolites Using Stable Isotopic Labeling and Fast Polarity-Switching LC–ESI-HRMS

Abstract: An untargeted metabolomics workflow for the detection of metabolites derived from endogenous or exogenous tracer substances is presented. To this end, a recently developed stable isotope-assisted LC–HRMS-based metabolomics workflow for the global annotation of biological samples has been further developed and extended. For untargeted detection of metabolites arising from labeled tracer substances, isotope pattern recognition has been adjusted to account for nonlabeled moieties conjugated to the native and labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 16 publications
(31 reference statements)
0
42
0
Order By: Relevance
“…Based on the result, it suggested that CE/TOF-MS study can be used as an option to replace the function of stable isotope labelling as carbon flow tracer in the plant. However, Kluger et al (2014) and You et al (2014) explained that stable isotope labelling is more effective to trace the metabolite element in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the result, it suggested that CE/TOF-MS study can be used as an option to replace the function of stable isotope labelling as carbon flow tracer in the plant. However, Kluger et al (2014) and You et al (2014) explained that stable isotope labelling is more effective to trace the metabolite element in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Orbitrap measurements were performed in positive and negative electrospray ionisation mode separately with a scan range from m/z 130 to 1300. All other mass spectrometric settings were concordant with those of Kluger et al [25]. Data were acquired and evaluated with Thermo Xcalibur 4.0.27.10 and 2.2 software (both Thermo Fisher Scientific), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The combination with stable isotopic labelling (SIL) offers to differentiate between biologically derived metabolites and unspecific signals coming from solvents, reagents, biological matrix, or instrument noise [23,24]. SIL-assisted metabolomics workflows were recently developed to study the metabolism of endogenous or exogenous tracer compounds in biological systems [25]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent LC-HRMS measurement and TracExtract version 2 [21] data processing resulted in 151 Phe-derived features, which were detected in the 13 C-Phe-treated sample. In order to increase the number of features on the reference list and thereby enhance m / z and Rt correction accuracy, plants of the same cultivar were also raised in a tailor made growth chamber with 13 C enrichment of 98.8% as well as under native 12 CO 2 atmosphere in parallel.…”
Section: Methodsmentioning
confidence: 99%